Frontiers in hardware security and trust theory, design and practice - Chang, Chip-Hong; Cao, Yuan (The Institution of Engineering and Technology, 2020)
The book consists of 15 chapters dealing with the following subjects: hardware security threats; IP/IC piracy threats of reversible circuits; persistent fault analysis on block ciphers; EMC techniques in design of IC chips; hardware obfuscation for IP protection; formal verification for SoC security; silicon-based true random number generators; micro-architectural attacks and countermeasures on public-key implementations; CACHEKIT attack mitigation; deep learning network security; nondigital components; homomorphic encryption; information leakage from robust codes protecting cryptographic primitives; confidential and energy-efficient cognitive communications; physical-layer security; mm-wave massive MIMO communications in 5G networks; and in-vehicle controller area network
Keywords: Computer security.; Internet of things.; Cell phone systems.; Cognitive radio networks.; Computer software -- Verification.; Industrial property.; Integrated circuits.; Machine learning.; Neural networks (Computer science); elektronické knihy; electronic books